Cryoultrasound therapy and tendonitis in athletes: a comparative evaluation versus laser CO2 and t.e.ca.r therapy - Costantino, C.; Pogliacomi, F.; Vaienti, E. (Acta Biomedica Atenei Parmensis, 2005)
Aim of this study is to compare the different kinds of tendonitis in athletes using cryoultrasound therapy, lasertherapy CO2 and t.e.ca.r. therapy ( transfert energetic capacitive and resistive ). Forty five athletes were selected; they were all affected by severe insertional tendonitis of the Achilles tendon (15 of them), of the patellar tendon (15 of them) and of the epicondylar region (15 of them) during the last two months. They were divided into three groups. The first group underwent a treatment of 12 lasertherapy CO2 sessions, the second group 12 cryoultrasound therapy sessions and the last group 12 t.e.ca.r. therapy sessions. Each patient was registered by an independent observer according to the pain before (initial V.A.S.) and after treatment (final V.A.S.) using the analogic visual range from 0 (lack of pain) to 10 (unbearable pain) and the indicator of efficacy (difference between initial V.A.S. and final V.A.S. / initial V.A.S.x 100). The obtained results were expressed as a difference between the two V.A.S. values and as a parameter of effectiveness (value ranging from 0 to 100) in order to correlate the initial condition of the patients with the performed physiotherapic treatment. The obtained V.A.S. score was submitted to statistic evaluation by analysis of variance through repeated measures, taking into consideration a value of p